Avaliação do processo de implementação do Programa Famílias Fortes na prevenção do uso de drogas entre adolescentes brasileiros - Santos, Luís Eduardo Soares dos (2023)
The evaluation of drug use prevention programs among adolescents goes far beyond analyzing effectiveness, efficiency and effectiveness. To this end, process evaluation of these programs is extremely necessary, as through it it is possible to determine which situations and mechanisms predict patterns of success and failure for their implementation. Therefore, the objective of this study is to evaluate the implementation process of the Brazilian version of theStrong Families Program (PFF 10-14) in preventing drug use among Brazilian adolescents in the model proposed by the Ministry of Women, Family and Human Rights (MMFDH). This is an evaluative research, with a qualitative approach, carried out at Social Assistance Reference Centers in 13 cities, distributed across five Brazilian states. 122 individuals participated in the study, 51 parents/guardians; 51 teenagers; nine implementers and 11 managers. Data collection was carried out from October 2021 to June 2022 through 57 observations, 16 focus groups, 20 interviews and 816 entries in the fidelity form. The data was analyzed using Bardin's Content Analysis and organized into three axes: implementation, impact mechanisms and context. The data was triangulated in order to elucidate the fidelity, feasibility and acceptability, in addition to the barriers and facilitators present in the implementation of the program. The results showed that the program's fidelity suffered variations in terms of the execution of activities, changes in activities and completion time. Regarding feasibility, implementers reported that the videos used were distant from Brazilian culture, reinforcing the need to adapt the material. Parents/guardians and adolescents highlighted behavioral changes such as reduced parental stress, strengthening family dialogue, greater understanding of the risks of drug use and strengthening refusal skills. Regarding acceptability, a gradual evolution of interest and interaction levels was observed in most meetings. Satisfaction with the printed material and the dynamics carried out were some of the positive aspects listed by the participants. The main barriers present in implementation were the precarious infrastructure of services, recruitment and access for families and difficulties in understanding the written material. The commitment and dedication of implementers and managers, combined with the support of municipal management, were considered the main facilitators. The evaluation of the implementation process of the Strengthening Families Program acted as a tool of fundamental importance in understanding the quality and quantity of what is delivered, that is, what is, in fact, put into practice when conducting the program; in addition to the perceptions and experiences of families and other actors involved, as well as the identification of the main barriers and facilitators present in its implementation.